2002
DOI: 10.1034/j.1398-9995.2002.203511.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sensitization to the predatory mite Amblyseius cucumeris as a new occupational allergen in horticulture

Abstract: The predatory mite Ac is a new occupational allergen in horticulture which can cause an IgE-mediated allergy in exposed employees. It is biologically active on the mucous membranes of the nose and therefore clinically relevant for the development of work-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In contrast, personal air samples were composed of sequences derived from the Ascomycota plant pathogen, Botrytis cinerea , the causal source of gray mold disease that affects cannabis stems and buds [59–61]. Previous occupational health studies have shown B. cinerea to be prevalent in greenhouse environments [62, 63] and worker exposure has been implicated in cases of allergy and hypersensitivity pneumonitis [64–69]. Other assessments of fungal communities associated with cannabis plants have been recently conducted within the cannabis industry.…”
Section: Occupational Fungal Community Analysismentioning
confidence: 99%
“…In contrast, personal air samples were composed of sequences derived from the Ascomycota plant pathogen, Botrytis cinerea , the causal source of gray mold disease that affects cannabis stems and buds [59–61]. Previous occupational health studies have shown B. cinerea to be prevalent in greenhouse environments [62, 63] and worker exposure has been implicated in cases of allergy and hypersensitivity pneumonitis [64–69]. Other assessments of fungal communities associated with cannabis plants have been recently conducted within the cannabis industry.…”
Section: Occupational Fungal Community Analysismentioning
confidence: 99%
“…Anaphylactic reactions were reported in 40% of 30 workers with occupational allergic urticaria caused by Thaumetopoea pityocampa (pine processionary caterpillar) [ 54 ]; thus, pinecone or resin collectors, woodcutters, farmers and stockbreeders were the most frequently and severely affected workers [ 7 ]. Greenhouse workers may develop a bumblebee venom allergy, because, in greenhouses, bumblebees are used for the pollination of plants [ 55 , 56 ]. Hymenoptera stings are specifically recognized as a high occupational risk for beekeepers (14–43%) [ 21 , 57 ]; the intense exposure to stings cause honeybee venom (HBV) to be the dominant allergen [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predatory mites are commonly used as biological pesticides worldwide for control of spider mites and other pests in greenhouses. In 1999, a study in bell pepper growers described the Amblyseius cucumeris as a relevant source of occupational allergy with 23% of the population having positive skin prick test reactions [ 28 ]. A subsequent work confirmed that Amblyseius cucumeris has both species-specific antigens and common antigens that are cross-reacting with D. Pteronyssinus [ 29 ].…”
Section: Discussionmentioning
confidence: 99%